الإلهيات عند الأشعري ( ت:324هـ) من خلال كُتُبه إثبات اليدين والعينين نموذجا دراسة وصفية نقدية: Affirmation of Allah Almighty’s Hands and Eyes in the Authored Works of al-Ashʿarī (d. 324 AH): A Critical Descriptive Study of the Divine Attributes in the Theology - حسن الخطاف (الدراسات الإسلامية, 2024)
Al-Ashʿarī is widely acknowledged as the preeminent figure and undisputed scholar of Ahl al-Sunnah. However, there is no scholarly consensus on the content and authenticity of the texts attributed to him. This study concentrates on analyzing the extant texts and accounts transmitted by his followers. Given Al-Ashʿarī’s influential status, the central question arises: Do these texts genuinely reflect his theological stance and that of Ahl al Sunnah? Do they demonstrate consistency with Qur’anic verses and Prophetic traditions, or do they represent a particular developmental stage in his thought, possibly affected by textual alterations or interpolations? The significance of this study lies in its ability to address these questions. The study is structured into two primary sections, using descriptive and critical methodologies. A significant finding of the study is the identification of a distinct literalist tendency in Al-Ashʿarī’s works, including Maqālāt al Islāmiyyīn, which frequently contradicts the semantic implications of the Arabic language employed in the Qur’an. This literalism also diverges from the methodological approaches of his followers, particularly regarding the affirmation of Allah’s physical attributes, such as eyes (ʿaynayn). Importantly, this literalism is not explicitly anthropomorphic but rather implied within the text. A notable consequence of this trend is the neglect of interpreting verses in the context of their revelatory context and thematic coherence.